Sybil - Schreiber, Flora Rheta; Petrie, Daniel; Davis, Brad.; Woodward, Joanne, 1930-; Field, Sally; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2006)
A landmark, classic drama depicting the extraordinary real life of a young woman suffering from multiple personality disorder.
English track: Dolby digital 2.0 surround.
Title from container.
From the book by Flora Rheta Schreiber.
Originally released as a motion picture in 1976.
Special features: retrospective documentary 'Examining Sybil'; Sybil therapy session; 'The paintings of Sybil'.
Brad Davis, Joanne Woodward, Sally Field.
Keywords: Multiple personality -- Drama; Psychiatrists -- United States -- Drama; Abused children -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Films for the hearing impaired; Suspense films